COMPUTER VISION SYSTEM FOR COLOR MEASUREMENTS OF MEAT AND MEAT PRODUCTS: A REVIEW - Igor B. Tomasevic (Теория и практика переработки мяса, 2018)
Meat and meat products color evaluation ability of a computer vision system (CVS) is investigated by a comparison study with color measurements from a traditional colorimeter. A statistical analysis revealed significant differences between the instrumental values in all three dimensions (L*, a*, b*) between the CVS and colorimeter. The CVS-generated colors were more similar to the sample of the meat products visualized on the monitor, compared to colorimeter-generated colors in all (100 %) individual trials performed. The use of CVS should be considered a superior alternative to the traditional method for measuring color of meat and meat products.